2000
DOI: 10.1021/jm0000259
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Kinase Inhibitors. 2. Synthesis, Enzyme Inhibition, and Antiseizure Activity of Diaryltubercidin Analogues

Abstract: In the preceding article (Ugarkar et al. J. Med. Chem. 2000, 43) we reported that analogues of tubercidin are potent adenosine kinase (AK) inhibitors with antiseizure activity in the rat maximum electroshock (MES) model. Despite the discovery of several highly potent AK inhibitors (AKIs), e.g., 5'-amino-5'-deoxy- 5-iodotubercidin (1c) (IC50 = 0.0006 microM), no compounds were identified that exhibited a safety, efficacy, and side effect profile suitable for further development. In this article, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 23 publications
7
71
0
Order By: Relevance
“…Among those pyrrolo[2,3-day]pyrimidine nucleoside analogs, the 59-amino-59-deoxy analogs of 5-bromo-and 5-iodotubercidin exhibited the highest potency and efficacy in the MES model (Ugarkar et al, 2000b). Although none of those compounds met a safety, efficacy, and side effect profile suitable for further drug development (Ugarkar et al, 2000a), substitution of the tubercidin molecule with aromatic rings at the N4 and C5 positions yielded highly potent ADK inhibitors with efficacy in the MES model and reduced side effects (Ugarkar et al, 2000a). Potency of nucleoside ADK inhibitors was significantly enhanced (e.g., 10-fold compared with 59-deoxy-59-aminoadenosine) in 6,8-disubstituted purine nucleosides (Bookser et al, 2005a).…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Among those pyrrolo[2,3-day]pyrimidine nucleoside analogs, the 59-amino-59-deoxy analogs of 5-bromo-and 5-iodotubercidin exhibited the highest potency and efficacy in the MES model (Ugarkar et al, 2000b). Although none of those compounds met a safety, efficacy, and side effect profile suitable for further drug development (Ugarkar et al, 2000a), substitution of the tubercidin molecule with aromatic rings at the N4 and C5 positions yielded highly potent ADK inhibitors with efficacy in the MES model and reduced side effects (Ugarkar et al, 2000a). Potency of nucleoside ADK inhibitors was significantly enhanced (e.g., 10-fold compared with 59-deoxy-59-aminoadenosine) in 6,8-disubstituted purine nucleosides (Bookser et al, 2005a).…”
Section: Pharmacologymentioning
confidence: 99%
“…Consequently, ADK inhibitors have been considered as a very attractive target for the treatment of various pain states, and proof of feasibility studies with prototypes of ADK inhibitors have demonstrated efficacy in several animal models of nociception (Keil and DeLander, 1994;Sawynok, 1995, 1998;Sawynok and Liu, 2003). Unfortunately, short half lives in vivo, poor bioavailability, lack of pharmacological selectivity, and potential to form cytotoxic metabolites limited further preclinical testing of those prototype inhibitors (Cottam et al, 1993;Wiesner et al, 1999;Ugarkar et al, 2000a). Therefore, most subsequent studies have focused on the structurally novel nucleoside (A-134974), nonnucleoside (ABT-702), and carbocyclic (A-286501) ADK inhibitors (Fig.…”
Section: B Applications In Preclinical Studiesmentioning
confidence: 99%
“…Inhibition of its activity enhances the release of adenosine from cells, and extracellular adenosine is known to act as a neuromodulator with potent anti-nociceptive and anti-inflammatory actions. Therefore, inhibition of AK activity is proposed as a therapeutic strategy for the treatment of pain, and inflammation and several potent inhibitors of AK activity have been reported (25)(26)(27). To analyze AK binding to BisIII beads, a myc-tagged version of AK was transiently expressed in COS-7 cells.…”
Section: Generation Of Pkc Inhibitor Affinitymentioning
confidence: 99%
“…These compounds suppress seizures in rodent models, such as the bicuculline-induced seizure [249] and the maximal electroshock [170,250,251] model, presumably via an interaction of adenosine with cerebral A 1 R. For that reason and because upregulation of the enzyme AK is involved in epileptogenesis [171], AKIs are considered promising anticonvulsants [170,252,253].…”
Section: Ak Inhibitorsmentioning
confidence: 99%